The Concept of Waste Management on Economic Development in the European Union - Azwardi, Azwardi; Imago, Alghifari Mahdi; Wijaya, Wahyu Aji (International Journal of Energy Economics and Policy, 2023)
This study aims to analyze whether the circular economy variables which include per capita municipal waste production, municipal waste recycling rate, packaging waste recycling rate by type of packaging, bio-waste recycling, and e-waste recycling rates have an effect on economic development. measured by GDP per capita (Gross Domestic Product) in European Union countries. The methodology in this study uses panel data with estimates using the common effect model, fixed effect model, random effect model and uses the best testing method, namely the Chow, Hausman, and Lagrange multiplier tests in 28 countries in the European Union for the period 2000-2020. The results showed that the final model used was the fixed effect model. Overall the concept of a circular economy which includes the level of recycling of municipal waste, the level of recycling of packaging waste by type of packaging, recycling of bio-waste, recycling of e-waste and added value in the Euro currency has a significant and positive effect on economic development as measured through per capita income, while waste production per capita is inversely proportional to that it has no significant and positive effect on economic development in European Union countries. It can be concluded that the application of the circular economy concept can ensure economic growth while reducing the use of natural resources and ensuring great environmental protection.